Studies in the carbazole series - Barclay, Bessie Munro (The University of Edinburgh, 1944)
(1) . The application. of the method of chloranil dehydrogenation to substituted tetrahydrocarbazoles, as well as to dihydrocarbazoie, hexahydrocarbazoLe, and to e substituted hexahydrocarbazoIe, here been worked out, and have led to the successful preparation many examples cf various types of substituted carbazoles. The list of carbazole derivatives so prepared includes several important compounds Which have never before been obtained, and all the .mono-bromo and mono-nitrocarbazole are now listed.

(2) . Borsche had already proved the wide scope of the application of the Fischer indole synthesis to the preparation of substituted tetrahydrocarbazoles, but no dehydrogenation agent could be found suitable for all cases, i.e. a reagent which had no effect on all the possible substituent groups, e.g. halogen -, nitro-, carboxy-, etc., etc. In the course of this research, the suitability of chloranil dehydrogenations in all cases bae been. proved, and during the discussion of experimental results, the superiority of chloranil over other dehydrogenation agents has been pointed out. The one disadvantage of this reagent - long period of reflux generally required - is certainly outweighed by its wide applicability and by the good yields of products obtained.

(3) During the investigations on the use of this dehydrogenation reagent, improved methods of preparation of the intermediate stages in the substituted tetrahydrocarbazole synthesis were introduced, and especially in the preparation of the substituted phenylbydrazines necessary for the syntheses.

All these improvements add to the efficiency of this highly satisfactory method of obtaining carbazole derivatives - by chloranil dehydrogenation of substituted tetrahydrocarbazoles.